Food parenting practices and eating behaviors in childhood: a cross-lagged approach within the Generation XXI cohort. Issue 1 (19th March 2021) - Costa, Alexandra; Severo, Milton; Oliveira, Andreia
ABSTRACT: Background: Food parenting practices have been associated with children's eating behaviors, but analyses exploring the bidirectional effects are limited. Objectives: We aimed to examine the bidirectional relations between food parenting practices and the eating behavior of children from 4 to 7 y old. Methods: Participants are from the Generation XXI birth cohort (Portugal) assessed at both 4 and 7 y of age ( n = 3698 singletons). A validated version of the Child Feeding Questionnaire and the overt/covert control scale were used. Three patterns of food parenting practices (Perceived Monitoring, Restriction, and Pressure to eat) were studied. Perception of children's eating behaviors (eating large amounts of food, eating very slowly, and food refusal) was reported by parents (measured using dichotomous questions). Cross-lagged analyses were performed to evaluate the direction of the associations (parenting practices at 4 y to behaviors at 7 y and the reverse). Results: Eating large amounts of food was unidirectionally associated with higher Restriction 3 y later (βstandardized = 0.047; 95% CI: 0.019, 0.075). Apart from Restriction, all associations had a bidirectional effect of similar magnitude. Eating large amounts of food and food refusal at age 4 influenced food parenting, such as Perceived Monitoring and Pressure to eat at age 7, but these practices were prospectively linked to these eating behaviors too (e.g., βstandardized = 0.033; 95% CI: 0.022, 0.064 for food refusal at age 4 and Pressure to eat at age 7, and βstandardized = 0.060; 95% CI: 0.034, 0.086, in the reverse direction). Parenting practices and children's eating behaviors showed significant moderate tracking (standardized path coefficients from 0.24 to 0.49). Conclusions: Eating large amounts of food, eating slowly, and food refusal can influence parents to adopt certain food parenting practices, but these practices also influence children's behaviors after a few years. This reciprocal relation should be considered in future research. Parents should be advised to use food parenting practices associated with healthier eating behaviors.